Leakage Detection in Water Pipes: An Approach of Smart Water - Dmitriy Vladislav (Big Data and Computing Visions)
This is an application of Wireless Sensor Network (WSN) to avoid the leakages, which are happening in the underground. It is quite hard to detect the leaks inside the ground, so this is a method which we can send some signals and detect where the leakage is happened and we can fix it easily. Our main aim is to detect the leakages happened in the water separation in water distribution network. To overcome this problem, we use the Smart Water Leakage Detection (SWLD) in pipelines. In this SWLD we measure water level in tank and control in pump to turn it on when the water level is less (low). The System contains 2 parts: the first part is alarm based on Global System for Mobile (GSM) technology to send Short Message Service (SMS) to the owner. This system is containing basic components like sensors, GSM module, Arduino. The second is the controlling part; it uses Android application mobile to control the pump.